Antithrombotic agents intake prior to injury does not affect outcome after a traumatic brain injury in hospitalized elderly patients. (April 2017) - Julien, Jessica; Alsideiri, Ghusn; Marcoux, Judith; Hasen, Mohammed; Correa, José A.; Feyz, Mitra; Maleki, Mohammed; de Guise, Elaine
Highlights: Age and severity of injury have an effect on the outcome following TBI. After a TBI, taking antiplatelet or anticoagulant agents has an effect on outcome. The use of antithrombotic agents does not correlate with a prolonged length of stay. Abstract: Background : The purpose of this study is to investigate the effect of risk factors including International Normalized Ratio (INR) as well as the Partial Thromboplastin Time (PTT) scores on several outcomes, including hospital length of stay (LOS) and The Extended Glasgow Outcome Scale (GOSE) following TBI in the elderly population. Methods : Data were retrospectively collected on patients ( n  = 982) aged 65 and above who were admitted post TBI to the McGill University Health Centre-Montreal General Hospital from 2000 to 2011. Age, Injury Severity Score (ISS), Glasgow Coma Scale score (GCS), type of trauma (isolated TBI vs polytrauma including TBI), initial CT scan results according to the Marshall Classification and the INR and PTT scores and prescriptions of antiplatelet or anticoagulant agents (AP/AC) were collected. Results : Results also indicated that age, ISS and GSC score have an effect on the GOSE score. We also found that taking AC/AP has an effect on GOSE outcome, but that this effects depends on PTT, with lower odds of a worse outcome for those taking AC/AP agents as the PTT value goes up. However, this effect only becomes significant as the PTT value reaches 60 and above. Conclusion : Age and injury severity rather than antithrombotic agent intake are associated with adverse acute outcome such as GOSE in hospitalized elderly TBI patients.